The Therapeutic Effects of Whole-Body Vibration in Patients With Fibromyalgia. A Randomized Controlled Trial - Mingorance, José A.; Montoya, Pedro; Miranda, José G. Vivas; Riquelme, Inmaculada (Frontiers in Neurology, 2021)
Fibromyalgia is a chronic pain disease with few effective therapeutic options. We evaluated the efficacy of a 12-weeks therapy program that involves the use of whole body vibration in patients with fibromyalgia. The experimental group (N = 20 patients) participated in a neuromuscular training with a rotational whole body vibration platform for 12 weeks. The control group (N = 20 patients) received no physiotherapy treatment. The following variables were assessed before, after and 3 months after the therapy program: Fibromyalgia impact questionnaire, pain intensity, quality of life, sensitivity measurements (pressure pain thresholds, vibration thresholds), motor function tasks (Berg scale, 6-min walk test, isometric back muscle strength), and static and dynamic balance. We found improvements in the indexes of functional disability, static equilibrium and vibration sensitivity and a reduction of pain sensitivity. Our results showed that the intervention group improved almost all parameters immediately after the therapy program, in contrast to the control group that showed no changes. These improvements were not maintained in the follow-up. The whole body vibration therapy can be an effective therapy in patients with fibromyalgia and it can improve symptomatology and quality of life in these patients.